Internal audit of the quality management system. Quantitative process evaluation - Аксёнова, Людмила Ивановна; Коваль, Геннадий Михайлович (Technology audit and production reserves, 2013)
We continue to investigate the methods of internal audit with the purpose of objective evaluation of the quality management system processes at engineering enterprise. For the first time, the approach to the quantitative evaluation of the products life cycle processes is proposed, where the key indexes of the process function as a measurement object are crucial to meet the quality requirements. The process evaluation criteria are related to the characteristics of products quality and are based on the meeting the consumer requirements at every stage of the production cycle. Thus, this evaluation index means not only the actual results of the process, but also the potential opportunities that this process provides using the adjacent process. The method of the index forming and evaluation process is based on the concept "Six Sigma" and taking into account the features of the engineering enterprise, is illustrated on a practical example. The proposed method of the process quantitative evaluation is more accurate than the expert opinion and allows to make reliable conclusions on the results of the IA (internal audit). This evaluation model can be used by industrial enterprises in order to improve the process efficiency, as well as to reduce the risks and improve the products quality guarantees.